The Effect of Internal Auditing on Fraud Prevention in State-Owned Enterprises - Andaningsih, IGP Ratih (Westscience Press, 2025)
This study investigates the impact of internal audits on fraud prevention in Indonesian state-owned enterprises (SOEs). Using a quantitative approach, data were collected from 105 respondents consisting of internal auditors, finance officers, and managers across various SOEs. A structured questionnaire employing a five-point Likert scale was used to measure the dimensions of internal audit (independence, competence, audit quality, and management support) and fraud prevention (control effectiveness, ethical culture, and monitoring mechanisms). Statistical analysis was conducted using SPSS version 25 through descriptive statistics, classical assumption tests, and simple linear regression. The results revealed that internal audits have a significant positive effect on fraud prevention, with a determination coefficient (R²) of 0.541, indicating that internal audit explains 54.1% of the variance in fraud prevention. The findings confirm that auditor competence, audit independence, and management support play a critical role in strengthening fraud prevention systems. This study supports the Agency Theory and Fraud Triangle Theory, emphasizing internal audit as an essential governance mechanism to mitigate fraud risk and enhance accountability in SOEs. The results provide theoretical and practical insights for policymakers and management to strengthen audit practices and ethical frameworks in public sector governance.